Phase evolution in Zr-doped preceramic polymer derived SiZrOC hybrids. Issue 7 (May 2020) - Anand, Rahul; Sahoo, Soumya Prakash; Nayak, Bibhuti B.; Behera, Shantanu K.
Abstract: The present work focuses on the phase evolution of SiZrOC ceramic hybrids derived from the doping of Zr in a phenyl-containing silsesquioxane based preceramic polymer in the temperature range of 800 °C–1300 °C. A commercially available polymethylphenylsilsesquioxane polymer was doped with 5–20 mol% of Zr (through alkoxide source), and cross-linked. Inert atmosphere pyrolysis of thus produced powders yielded black colored SiZrOC ceramics. It was revealed that the dopants phase separate into t-ZrO2 beyond 800 °C. The crystallite size of t-ZrO2 was calculated from the X-ray diffractograms using Scherrer formula. Raman spectroscopy was employed to study the effect of dopant ion on retention of carbon and silica residual phases in the final ceramic hybrid. The crystallites of ZrO2 were further analyzed by high resolution transmission electron microscopy. The characterizations of Zr doped SiOx Cy ceramic hybrids exhibit potential for coating systems in moderate to high temperature applications.